Risk and Protective Factors for Personality Disorders: An Umbrella Review of Published Meta-Analyses of Case–Control and Cohort Studies - Solmi, Marco; Dragioti, Elena; Croatto, Giovanni; Radua, Joaquim; Borgwardt, Stefan; Carvalho, Andre F.; Demurtas, Jacopo; Mosina, Anna; Kurotschka, Peter; Thompson, Trevor; Cortese, Samuele; Shin, Jae Il; et al. (Frontiers in Psychiatry, 2021)
The putative risk/protective factors for the several personality disorders remain unclear. The majority of studies has assessed personality characteristics/traits rather than disorders. Thus, the current umbrella review of meta-analyses (MAs) aims to systematically assess risk/protective factors associated with personality disorders. We searched Pubmed-MEDLINE/PsycInfo databases, up to August 31st, 2020. Quality of MAs was assessed with AMSTAR-2, while the credibility of evidence for each association was assessed through standard quantitative criteria. Out of 571 references, five meta-analyses met inclusion criteria, encompassing 56 associations of 26 potential environmental factors for antisocial, dependent, borderline personality disorder, with a median of five studies per association, and median 214 cases per association. Overall, 35 (62.5%) of the associations were significant. Six associations met class II (i.e. highly suggestive) evidence for borderline personality disorder, with large effect sizes involving childhood emotional abuse (OR=28.15, 95%CI 14.76-53.68), childhood emotional neglect (OR=22.86, 95%CI11.55-45.22), childhood any adversities (OR=14.32, 95%CI 10.80-18.98), childhood physical abuse (OR=9.30, 95%CI 6.57-13.17), childhood sexual abuse (OR=7.95, 95%CI 6.21-10.17) and childhood physical neglect (OR=5.73, 95%CI 3.21-10.21), plus sixteen further associations supported by class IV evidence. No risk factor for antisocial or dependent personality disorder was supported by class I, II, III, but six and seven met class IV evidence, respectively. Quality of included meta-analyses was moderate in two, critically low in three. The large effect sizes found for a broad range of childhood adversities suggest that prevention of personality disorders should target childhood-related risk factors. Larger cohort studies assessing multidimensional risk factors are needed in the field.